Necesidad de reformar el art. innumerado 5 del título v, del libro II de la ley reformatoria al código orgánico de la niñez y adolescencia. - Erazo Narváez, Carlos Alfredo (2011)
The development of this research study to the Code of Children and Adolescents should be noted that subsidiary grandparents as required in the provision of food and not be the first priority, but on the contrary as a last resort, noting the age at who are entering, which provide food when they are or have a stable job and sufficient, for saying in regard to their economic capacity, does not mean you have that ability when they usually live on a pension and not a job that the circumstances of his grandparents old age because they usually come to a group of people who have special rights to be together with children and adolescents priority groups who need special attention. In this study, we analyzed in detail, which includes conceptualization, including the right of the people a priority groups, the nature and characteristics of the right food. Since the beginning of this legal right in society, it is necessary to establish substantial changes to the regulations of food law, in determining the priorities and subsidiary required to pay for food. This study of the benefit payment subsidiary of food comes from what is stated in Article unnumbered 5 of Title V, Book II The Law Amending the Code of Children and Adolescents, in which it is determined that the grandparents will be the first subsidiary required to pay maintenance, the latter being regarded as priority groups are not able to pay for food, because at this age, these people do not work and live on a pension retire and not a salary, circumstances leading to that subsidiary obligation to pay maintenance is performed only when more of their skills enough, they should be the last people to force them to pay for food, not the first priority, and also be taken into account the constraints The right to alimony in a subsidiary, the grandparents may not be the first priority, allows a moral benefit to the economic capacity of the required, effective protection of the principle of humanity, and interest for priority attention of adults and older adults about their livelihood, housing, health, clothing, medical care and recreation.